(y+4)(3y-2)=-y-14

Simple and best practice solution for (y+4)(3y-2)=-y-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+4)(3y-2)=-y-14 equation:


Simplifying
(y + 4)(3y + -2) = -1y + -14

Reorder the terms:
(4 + y)(3y + -2) = -1y + -14

Reorder the terms:
(4 + y)(-2 + 3y) = -1y + -14

Multiply (4 + y) * (-2 + 3y)
(4(-2 + 3y) + y(-2 + 3y)) = -1y + -14
((-2 * 4 + 3y * 4) + y(-2 + 3y)) = -1y + -14
((-8 + 12y) + y(-2 + 3y)) = -1y + -14
(-8 + 12y + (-2 * y + 3y * y)) = -1y + -14
(-8 + 12y + (-2y + 3y2)) = -1y + -14

Combine like terms: 12y + -2y = 10y
(-8 + 10y + 3y2) = -1y + -14

Reorder the terms:
-8 + 10y + 3y2 = -14 + -1y

Solving
-8 + 10y + 3y2 = -14 + -1y

Solving for variable 'y'.

Reorder the terms:
-8 + 14 + 10y + y + 3y2 = -14 + -1y + 14 + y

Combine like terms: -8 + 14 = 6
6 + 10y + y + 3y2 = -14 + -1y + 14 + y

Combine like terms: 10y + y = 11y
6 + 11y + 3y2 = -14 + -1y + 14 + y

Reorder the terms:
6 + 11y + 3y2 = -14 + 14 + -1y + y

Combine like terms: -14 + 14 = 0
6 + 11y + 3y2 = 0 + -1y + y
6 + 11y + 3y2 = -1y + y

Combine like terms: -1y + y = 0
6 + 11y + 3y2 = 0

Factor a trinomial.
(3 + y)(2 + 3y) = 0

Subproblem 1

Set the factor '(3 + y)' equal to zero and attempt to solve: Simplifying 3 + y = 0 Solving 3 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + y = 0 + -3 y = 0 + -3 Combine like terms: 0 + -3 = -3 y = -3 Simplifying y = -3

Subproblem 2

Set the factor '(2 + 3y)' equal to zero and attempt to solve: Simplifying 2 + 3y = 0 Solving 2 + 3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3y = 0 + -2 3y = 0 + -2 Combine like terms: 0 + -2 = -2 3y = -2 Divide each side by '3'. y = -0.6666666667 Simplifying y = -0.6666666667

Solution

y = {-3, -0.6666666667}

See similar equations:

| -2(14q-20)-4=-4(7q-9) | | 0.8-z=2.1 | | 15x-2-6x=45 | | (2x-3)+(7x+21)=90 | | 13x-29=155 | | -9.39-3.4d=-1.1d | | x^2-3xy+3y^2+6y=7 | | 4x+4z-2y=-1 | | 7(X-6)= | | b-7=12# | | (3X)9=24 | | (3X)9=25 | | 0=-3x^2+4x | | X+2015=Y | | 4m+5=48 | | (2x-3)=90 | | P-25=-53 | | 6x+7x-5x=-48 | | 6y=5y-8.6 | | (2x-3)=180 | | x^3+(2-i)x^2+(-4-3i)x+(1+i)=0 | | 6g=18# | | -2(y+1)=-4y+10 | | [2x-1]=3x | | 36=(x-1)2+(y-5)2 | | 7y-c=b | | -7=2(w-6)-7w | | x^2-2k(1+3k)+7(3+2k)=0 | | n+(n-8)=n+15 | | 3x-a=c | | 3.5-x=9 | | x+4y=59 |

Equations solver categories